2016
DOI: 10.1371/journal.pone.0145520
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Neuroticism, Hopelessness, and Depression in Older Korean Immigrants

Abstract: PurposeThis study aimed to investigate the relationship between neuroticism, hopelessness, and depression among older Korean immigrants. To extend this line of research, this study aimed to examine the effects of neuroticism and hopelessness in predicting depression among older Korean immigrants.MethodsData for this study came from a survey of 220 first generation Korean immigrants aged 65 years or older in Los Angeles County in 2012. Data were collected by face-to-face interviews with trained social workers u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
9
0
4
Order By: Relevance
“…To this scenery, the study adds some preventive measures that could reduce the feeling of hopelessness in this population, such as the implementation of policies for the extension of employment, support for the maintenance of quality education for immigrant children, community engagement programs, and the use of the BHS to track potential suicide risks in this population. Some of the limitations found in this study by Kim et al, 9 correspond to the difficulty of the sample being widespread for other populations of Asian Elderly people from the Americans or for Korean elderly in another context due to the population size of the sample being relatively small; the fact that the study is of transversal type makes it impossible to confirm causality among the analyzed variables and that some variables that could interfere with levels of neuroticism and hopelessness such as stress were not included. It has also not been taken into consideration that the Beck Hopelessness Scale may vary between clinical and nonclinical groups.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…To this scenery, the study adds some preventive measures that could reduce the feeling of hopelessness in this population, such as the implementation of policies for the extension of employment, support for the maintenance of quality education for immigrant children, community engagement programs, and the use of the BHS to track potential suicide risks in this population. Some of the limitations found in this study by Kim et al, 9 correspond to the difficulty of the sample being widespread for other populations of Asian Elderly people from the Americans or for Korean elderly in another context due to the population size of the sample being relatively small; the fact that the study is of transversal type makes it impossible to confirm causality among the analyzed variables and that some variables that could interfere with levels of neuroticism and hopelessness such as stress were not included. It has also not been taken into consideration that the Beck Hopelessness Scale may vary between clinical and nonclinical groups.…”
Section: Resultsmentioning
confidence: 68%
“…8 They used, in a sample of 79 elderly people, a socio-demographic questionnaire and questions about reading behavior and the use of the internet/computer, which is the main approach to be correlated with hopelessness in the elderly. Beck's Hopelessness Scale was used, composed of 20 sentences of true or false that classify the level of hopelessness at the minimum level of hopelessness (0-3), mild level of hopelessness (4)(5)(6)(7)(8), moderate level of hopelessness (9)(10)(11)(12)(13)(14) and serious level (greater than 14). Finally, a question was made on the Reading Attitude Scale, composed of 30 assertions related to reading behavior in which maximum score is 120 points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most frequent mental health problems among the elderly is depression, and available evidence consistently suggests that depression is associated with feelings of hopelessness [3,4]. For example, Kim et al [4] explored the relationship between neuroticism, hopelessness, and depression among older Korean immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequent mental health problems among the elderly is depression, and available evidence consistently suggests that depression is associated with feelings of hopelessness [3,4]. For example, Kim et al [4] explored the relationship between neuroticism, hopelessness, and depression among older Korean immigrants. The results of a study conducted in 2012 in Los Angeles County, in which 220 first generation Korean immigrants aged 65 years or older participated, showed that older Korean immigrants with severe neuroticism and higher levels of hopelessness were more likely to experience higher levels of depression.…”
Section: Introductionmentioning
confidence: 99%